2010
DOI: 10.1016/j.febslet.2010.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a putative acetoin dehydrogenase complex in the hyperthermophilic archaeon Sulfolobus solfataricus

Abstract: Edited by Stuart FergusonKeywords: Acetoin 2-Oxoacid dehydrogenase complex Archaea Thermophile Metabolism a b s t r a c t Like many other aerobic archaea, the hyperthermophile Sulfolobus solfataricus possesses a gene cluster encoding components of a putative 2-oxoacid dehydrogenase complex. In the current paper, we have cloned and expressed the first two genes of this cluster and demonstrate that the protein products form an a 2 b 2 hetero-tetramer possessing the catalytic activity characteristic of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These data also suggest that P. furiosus is unable to take up acetoin, since the concentration of acetoin continues to rise throughout the growth phase for the COM1c and AHDA strains. Only one archaeon, Sulfolobus solfataricus, has been reported to utilize acetoin as an energy source and, although it contains an als homolog similar to P. furiosus als, it is not known to produce acetoin (22).…”
Section: Als Is Responsible For Acetoin Formation In P Furiosusmentioning
confidence: 99%
“…These data also suggest that P. furiosus is unable to take up acetoin, since the concentration of acetoin continues to rise throughout the growth phase for the COM1c and AHDA strains. Only one archaeon, Sulfolobus solfataricus, has been reported to utilize acetoin as an energy source and, although it contains an als homolog similar to P. furiosus als, it is not known to produce acetoin (22).…”
Section: Als Is Responsible For Acetoin Formation In P Furiosusmentioning
confidence: 99%
“…The initial step of acetoin breakdown was catalysed by AoDH ES E1 in the catabolic pathway of acetoin in bacteria [4]. Only AoDH ESs from mesophilic bacteria were characterized before Payne et al [39] reported the AoDH ES from a hyperthermophilic archaeon Sulfolobus solfataricus with an optimum temperature of 80°C. This study thus provided an example of a moderately thermophilic AoDH ES.…”
Section: Discussionmentioning
confidence: 99%
“…A second lipoylated complex with activity related to PDH is the acetoin dehydrogenase complex (AoDH); like PDH, AoDH also produces acetyl-CoA. AoDH is only found in bacteria, and is responsible for the catabolism of the acetoin energy storage molecule into acetyl-CoA and acetylaldehyde [23,24].…”
Section: Metabolic Roles Of Lipoylated Complexesmentioning
confidence: 99%